Sign in
Please select an account to continue using cracku.in
↓ →
The inverse of the proposition $$(p \wedge \sim q) \rightarrow r$$ is
$$(p \wedge \sim q) \rightarrow \sim r$$
$$(\sim p \vee q) \rightarrow \sim r$$
$$(\sim p \wedge q) \rightarrow \sim r$$
$$(p \vee \sim q) \rightarrow \sim r$$
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Detailed syllabus & Topic-wise Weightage
By proceeding you agree to create your account
Free CAT Syllabus PDF will be sent to your email address soon !!!